2022
DOI: 10.5713/ab.21.0044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary pumpkin (Cucurbita moschata) seed meal on layer performance and egg quality characteristics

Abstract: Objective: The objective of this study was to investigate the of dietary pumpkin (Cucurbita moschata) seed meal (PSM) on laying performance, quality, fatty acids, cholesterol, antioxidant compounds and shelf life of eggs.Methods: Eighty Tetra SL laying hens, 50-week-old, were randomly divided into two equal groups, having 10 replicates with 4 birds in each. The control (CON) treatment was fed with basal diet, while experimental treatment was fed a diet with 9% pumpkin seed meal (PSM), for a 6 weeks period.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Literature data revealed that much attention has been given to the application of different feed additives to improve performance and, the quality of freshly laid eggs, showing that limited data are available on the effects of antioxidants in the diets of laying hens and on the preservation of egg quality during storage. Other natural antioxidants of plant origin, like green tea, rapeseed oil, acai lump, pumpkin seeds, and natural astaxanthin [ 22 , 71 , 74 , 75 , 76 ], were very effective in preserving the shelf-life of eggs, including albumen and yolk quality during storage at different times and temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature data revealed that much attention has been given to the application of different feed additives to improve performance and, the quality of freshly laid eggs, showing that limited data are available on the effects of antioxidants in the diets of laying hens and on the preservation of egg quality during storage. Other natural antioxidants of plant origin, like green tea, rapeseed oil, acai lump, pumpkin seeds, and natural astaxanthin [ 22 , 71 , 74 , 75 , 76 ], were very effective in preserving the shelf-life of eggs, including albumen and yolk quality during storage at different times and temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The egg quality parameters that influence the shelf-life of the eggs: egg weight (g), albumen weight (g), yolk weight (g), shell weight (g), eggshell thickness (mm), eggshell breaking strength (kf), albumen pH, yolk pH, yolk color and Haugh units, from fresh and stored eggs were determined as previously presented [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…During the 42 experimental days (6 weeks), egg production (%), average daily feed intake (g/day/layer), feed conversion ratio (g feed/g egg mass), laying percentage (%), and average egg weight (g/day), were monitored. Egg quality traits were determined as previously reported 55 . Briefly, by collecting 54 eggs (18 eggs/group) on last day of the trial, with homogenous weight and used to determine the physical quality parameters of the eggs: weight of the egg and its constituents (albumen, yolk, shell) with a Kern Precision Electronic Balance; Haugh Unit, an indicator of albumen quality was determined using an Egg Analyzer TM (ORKA Food Technology Ltd.), eggshell thickness, measured with an Egg Shell Thickness Gauge (Sanovo Engineering A/S, Denmark) and eggshell breaking strength, using an Egg Force Reader (Sanovo Engineering A/S, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…The statistical model was applied as reported previously 55 . One-way analysis of variance (ANOVA), using STATVIEW for WINDOWS (SAS, version 6.0) was carried out to determine the effect of diets on egg quality parameters, fatty acid composition, total polyphenols and antioxidant content in eggs.…”
Section: Methodsmentioning
confidence: 99%
“…They also have a good amount of vitamins and minerals, essential for physiological and biological functions in poultry [116][117][118][119][120][121][122]. Moreover, they contain phenolic components (phytochemicals) that are responsible for their high antioxidant capacity [116][117][118][119][120][121][122][123][124]. Pumpkin and garden cress seeds are also rich in polyphenols, flavonoids, antioxidants, and PUFA [125].…”
Section: Pumpkin (Cucurbita Maxima) and Garden Cress (Lepidium Sativum)mentioning
confidence: 99%